OBSESSIONS AND MANIFESTATIONS OF WOMEN'S IDEALISTIC ATTITUDE IN CHARACTERS NENEK TOWARD THE DECADENCE OF ENVIRONMENTAL EDUCATION VALUES: A Study of the Mimesis Paradigm in the Novel Nenek hebat dari Saga By Yoshici Shimada - Erni Erni; Noni Andriyani (Kafa`ah: Journal of Gender Studies, 2022)
The problem of natural disasters is a form of human inability to understand environmental ethics. The tendency of natural disasters that occur is caused by humans. Humans as creatures who are equipped with thoughts and are believed to be leaders still violate the provisions that apply in tradition. The purpose of this study is to reveal the obsession and idealistic manifestation of women in the ‘Nenek” character in the novel Nenek Hebat dari Saga by Yoshici Shimada. In addition, this study also describes the values of environmental education contained in the novel Nenek Hebat dari Saga from Yoshici Shimada's as the foundation of environmental education. The data in this study are in the form of words, phrases, clauses, sentences, the interpretation of which is believed to contain the values of environmental education. The data source of this research is a children's novel with the title Nenek Hebat dari Saga by Yoshici Shimada. The results showed that there are five values of environmental education contained in the novel Nenek Hebat dari Saga by Yoshici Shimida, namely: the value of environmental education on responsibility, the value of environmental education of compassion and concern for nature, the value of not harming, the value of living simply and in harmony with nature, and the value of democratic environmental education. Therefore, it can be concluded that the obsession of the ‘Nenek” figure in overcoming the decline in environmental education values can be used as the foundation of environmental education so that humans can live an easy and ethical life. Thus, this research can provide input to teachers and parents in providing reading material to children that can provide awareness for children about the importance of preserving the environment.